The use of the Sign Language by the Family of Deaf and Hearing Disabilies: a problematization necessary (Research, Society and Development, 2023)
This study aims to identify the knowledge of sign language by the parents of deaf and hearing impaired students of the Special School Professor Alfredo Dub and the influence of this in the development of their children. Therefore, in addition to bibliographic research, a questionnaire was applied as a data collection instrument, which was answered by a group of relatives of deaf children in a literacy process, in order to identify which conceptions they express about the language of their children and seeking to ascertain the interference of language learning by them in the cognitive development of these children. This article is divided into five topics, highlighting the presentation of the school where the study was carried out, the defense of the methodological theoretical proposal that is anchored in qualitative research, considering the bibliographical approach and the exploratory investigation, a brief analysis of the Brazilian Sign Language as mother tongue of the deaf from birth, the family of the deaf as a significant support for the student's learning and, finally, the parents' understanding of the challenges in educating a deaf child.